Leukoplakia of the oral mucosa and red border of the lips. Tactics of managing patients on an outpatient basis - Larisa I. Glebova; Ekaterina V. Zadionchenko (LLC "MEDIAFORMAT", 2022)
More than six years at the department of skin and veneer diseases of Yevdokimov Moscow State University of Medicine and Dentistry patients with pathology of the oral mucosa and the red border of the lips are treated. One of the most common pathologies of the oral mucosa and lips is leukoplakia, which occurs in a variety of clinical forms. In this article, the staff of the department shares with practitioners their observations of this group of patients and the tactics of their management on an outpatient basis.